Motivation of students with the weakened health to independent employments by a physical culture in the institute of higher - Подоляка [Anastasiya Podolyaka] Анастасія Євгеніївна; Безніс [O. Beznis] О. Є. (Slobozhanskyi Herald of Science and Sport, 2013)
A research purpose was a study of features of influence organizationally-methodical terms of construction of process of physical education in the institute of higher on forming of motivation of students to employments by physical exercises. The comparative analysis of features of organization and maintenance of the system of physical education is conducted in the different institutes. The questionnaire questioning of students is conducted. During the questionnaire questioning motivational priorities of students of different institutes of higher are studied in the field of physical culture and sport. Their attitude is certain toward the operating in the institute of higher system of physical education.